Permainan Tradisional Egrang Untuk Meningkatkan Keterampilan Sosial Dan Kecerdasan Kinestetik Anak SD - Afakhrul Masub Bakhtiar; Arya Setya Nugroho (EduStream: Jurnal Pendidikan Dasar, 2017)
Civilizing traditional game local wisdom through the younger generation, and patenting intellectual property is the long-term goal that the researcher wants to realize. Traditional games which are one of the nation's intellectual property, contain very conditions for the meaning of life. In specific targets, researchers want to improve the social skills and kinesthetic intelligence of elementary school children through traditional "Egrang" games. With the adoption of the traditional "Egrang" game in learning, it will automatically introduce and cultivate local wisdom in elementary school children. To achieve the target of increasing social skills and kinesthetic intelligence of elementary school children through the traditional game "Egrang", researchers conducted classroom action research collaborating with Slempit 1 Elementary School teachers, Kedamean, Gresik. This study uses cycle stages in Classroom Action Research, with each cycle having the stages: (1) planning; (2) implementation; (3) observation; and (4) reflection. This research was carried out at Slempit 1 State Primary School, Kedamean District, Gresik Regency, East Java Province. Data collection techniques were carried out by observation, questionnaire, and interview techniques. Data analysis techniques used qualitative and quantitative descriptive. The results of this study are traditional games of Egrang can improve social skills and kinesthetic intelligence of elementary school children.